Religion in the Afrosphere: The Constitution of a Blogging Counterpublic. (October 2015) - Boutros, Alexandra
The Afrosphere is a diverse field of social media marked by a willingness to engage issues of shared or collective concern for inhabitants of the "Black Atlantic" or the "Black diaspora." By looking at blogs as a form of public address, this analysis examines instances of religion in the Afrosphere as components of strategic identification around what Stephan Palmié terms "black collective selfhood." Considering both the technological affordances and cultural contexts of blogging, this analysis explores the intersection of race and religion in the Afrosphere as constitutive of digital counterpublic discourse. Building on textual analysis of blog posts, this analysis outlines how meaning is formed, fixed, and contested in discussions of religion in the Afrosphere. This analysis argues that the intersection of race and religion within this digital counterpublic makes particular iterations of the Black diaspora visible.